2016
DOI: 10.1002/maco.201609174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flue gas composition on deposit induced high temperature corrosion under laboratory conditions mimicking biomass firing. Part II: Exposures in SO2 containing atmospheres

Abstract: In biomass fired power plants, the fast corrosion of superheaters is facilitated by the presence of corrosive flue gas species, for example, SO2, which are released during combustion. To understand the role of the gas species on the corrosion process, comparative laboratory exposures of deposit (KCl)‐coated and deposit‐free austenitic stainless steel (TP 347H FG) samples to gas mixtures containing SO2 was carried out, under conditions relevant to biomass‐firing. Exposures were conducted isothermally at 560 °C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In the first part of this study (Part I, present paper), results from corrosion exposures of both deposit‐coated and deposit‐free samples to oxidizing and oxidizing‐chlorinating gas mixtures are reported. In the accompanying paper (Part II, same journal volume) , results from exposure of deposit‐coated and deposit‐free samples to sulfidizing gas mixtures (with and without hydrogen chloride (HCl)) are presented and discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In the first part of this study (Part I, present paper), results from corrosion exposures of both deposit‐coated and deposit‐free samples to oxidizing and oxidizing‐chlorinating gas mixtures are reported. In the accompanying paper (Part II, same journal volume) , results from exposure of deposit‐coated and deposit‐free samples to sulfidizing gas mixtures (with and without hydrogen chloride (HCl)) are presented and discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…A series of investigations were conducted in a gaseous environment (6 %O 2 , 12 %CO 2 , 82 %N 2 , 400 ppm HCl, 60 ppm SO 2 ) and varying amounts of H 2 O with the use of KCl deposit to mimic the biomass corrosion 56,57,58 . A deposit of KCl was applied as a slurry according to EU guidelines, which after drying was characterized as a compact layer.…”
Section: Results From Laboratory Studies Flue Gas Parametersmentioning
confidence: 99%
“…Another interesting observation was that increased water vapor content decreased the amount of attack measured 57 . In addition, when HCl gas was not in the gas mixture, a thick potassium sulfate layer was present, and underneath there was deep pitting reminiscent of reducing conditions observed in coal gasifiers 58 . Earlier results in the same equipment but where the deposit was applied as a powder did not reveal deep sulfidation pitting.…”
Section: Results From Laboratory Studies Flue Gas Parametersmentioning
confidence: 99%
“…Upon dissociation of HCl via the Deacon process [47][48][49], Cl2 is generated and can propagate the corrosion attack by chlorination of the alloying elements at the corrosion front, where the oxygen partial pressure is relatively low. Although the HCl originally present in the gas mixture also has the tendency of inducing chlorination attack by itself, previous studies [50,51] have shown that this has a lower influence on the degree of corrosion attack, compared to corrosion attack in the presence of KCl deposits.…”
Section: Discussionmentioning
confidence: 97%